THE CORRELATION BETWEEN INTEREST IN READING ENGLISH TEXTS AND READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS OF SMAN BINAAN KHUSUS KOTA DUMAI - Restiana, Novia; Purwanti, Indah Tri; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed at exploring the correlation between interest in reading English texts and reading comprehension of the eleventh grade students of SMAN Binaan Khusus Kota Dumai. A correlational research design was used in this research. Two classes cosisting of 60 students were chosen by using cluster random sampling. There were two data obtained in this research: the percentage of students' interest in reading English texts and their reading comprehension test score. The questionnaire was used to discover the students' interest in reading English texts while reading comprehension tests were used to acknowledge their reading comprehension score. The results showed that the r-obtained was 0.619 with the significant level at 0.05 which means that there was a correlation between interest in reading English texts and reading comprehension. The value of R square showed that the range percentage between interest in reading English texts and reading comprehension of the students was 38.3%. In other words, it was implied that the higher the students' interest in reading English texts, the higher reading comprehension scores they might get.Key Words: Correlation, Interest in Reading English Texts, Reading Comprehension